MEDAN MAKNA VERBA CUT DALAM BAHASA INGGRIS - Oktaviana, Ika; Lapiana, Ummi Nurjamil Baiti; Felayati, Safrina Arifiani; Liambo, Eka Yunita (Universitas Ahmad Dahlan, 2023)
This study discusses meaning field of verb cut in English. This study is aimed at finding out the lexemes of verb cut and the semantic features contained in each lexeme. The data source for this study is obtained from the research results of Levin (1993) and the iweb corpus. The data of this research only takes lexemes mentioned as group member of verb cut. The data are collected is by finding and writing off groups of cut verbs contained in the book and the corpus. Then after being collected, the data was analyzed by looking for definitions of the group of cut verbs from three dictionaries, namely the Oxford Dictionary of English, Merriam Webster Dictionary, and Longman English Dictionary. After that, the data were analyzed according to the components of meaning contained in the verb cut group. The results of this study indicate that there are 18 lexemes as members of verb cut and there are four semantic features consisting of activity, instrument, object and result features.